The Global Prevalence of Schistosoma mansoni, S. japonicum, and S. haematobium in Pregnant Women: A Systematic Review and Meta-Analysis - Leslie Faye T. Cando; Glenmarie Angelica S. Perias; Ourlad Alzeus G. Tantengco; Micah D. Dispo; Jeremy A. Ceriales; Mark John G. Girasol; Lydia R. Leonardo; Ian Kim B. Tabios (Tropical Medicine and Infectious Disease, 2022)
Schistosomiasis is a neglected tropical disease affecting 40 million women of childbearing age worldwide. Its global disease prevalence among pregnant women is still unknown. This meta-analysis determined the pooled prevalence of schistosomiasis among pregnant women globally. Additionally, this study also determined the pooled prevalence based on infection intensity based on eggs per gram. Observational studies on the prevalence of schistosomiasis among pregnant patients were obtained from Medline, Scopus, and CINAHL from January 2001 until August 2020. A review of titles and abstracts was done independently by six reviewers. The quality of the included studies was assessed using the Newcastle–Ottawa Scale for case–control, cohort, and cross-sectional studies. A total of 27 studies were included in the meta-analysis and meta-regression. The pooled prevalence of S. haematobium was 13.44 (CI: 8.90–19.80) per 100 observations, while the pooled prevalence of S. mansoni was 12.18 (CI: 4.47–29.12) per 100 observations. The prevalence of S. japonicum infection in one study was 53.54 (CI: 43.23–63.62) per 100 observations. Our results showed a prevailing health problem of schistosomiasis during pregnancy in various countries worldwide. This strengthens the need to conduct more schistosomiasis research, prevention, and control programs in pregnant women.